Investasi Asing di Kalimantan Timur dalam Kerjasama Bilateral: Tinjauan Melalui Perspektif Rational Choice - Rahmah Daniah (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2014)
Natural resources (SDA) potential in East Kalimantan (Kal-Tim) has a significant value, such as high income-tax local, until investors attended, specifically South Korea and Rusia. This article elaborates the concept of “Rational Choice”, which is analysis about cost, benefit, risk and how to minimize risk host country in alternative decisions. Therefore, as argued in this article, investors had positive and negative impacts to local development. Keywords : East Kalimantan, Impact, Investor, Rational Choice